Ustʹi︠a︡ r. Ireti po opisi Gidrograficheskoĭ Ėkspedit︠s︡īi Vostochnago ok. 1912 g. / Sʺemka i chernīe Shturmana d. pl. Ivanovskago - Russia. Glavnoe gidrograficheskoe upravlenīe (Vladivostok : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; Владивосток : Морское министерство, Главное гидрографическое управленіе, 1912)
Relief shown by hachures, spot heights and form lines. Depths shown by soundings and isolines.; Title translation: The mouth of the Iret river according to the survey of the Hydrographic Expedition of the Pacific Ocean 1912 Grayscale;